BIOCHEMICAL AND ANTIBACTERIAL POTENTIAL OF AUTOCHTHONOUS CARNOBACTERIUM AND LACTOBACILLUS SPECIES ISOLATED FROM GASTROINTESTINAL TRACT OF COASTAL FISH - F. Sahnouni; E. Ringø; A. Maizi; S. Belmaghnia A. Matallah-Boutiba; D. Chemlal; Z. Boutiba (Journal of Animal and Plant Sciences, 2016)
A study was conducted to characterize 30 autochthonous lactic acid bacteria (LAB) strains isolated from the gastrointestinal (GI) tract of three fish species; Atlantic horse mackerel(Trachurus trachurus), European pilchard (Sardina pilchardus)andAtlantic bonito (Sarda sarda), on the basis of phenotypic characters. The strains were characterized according to their potential properties; antimicrobial activity, acidifying capacity, proteolytic and  lipolytic activity and they belonged to; Lactobacillus plantarum, L. sakei, L. coryniformis, L. fermentum, L. oris and Carnobacterium spp. All strains revealed inhibitory activities against one or more of the following target strains: Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC25922), Pseudomonas aeruginosa (ATCC27853), Bacillus cereus (LRSE 01), Aeromonas hydrophila (LRSE 04), Listeria innocua (LRSE 12), Salmonella sp. (LRSE 05)and Vibrio sp. (LRSE 23). Characterization of the antimicrobial substances showed that 4 out of 30 produce bacteriocin-like substances. The majority of the strains (26) revealed weak acidification, 15 strains were able to hydrolyze casein and twenty six out of 30 LAB strains revealed lipolytic activity .
Keywords: costal fish; Lactobacillus; Carnobacterium; Potential properties